2009
DOI: 10.1149/1.3080639
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Dynamics of Activated Hydrophobic Silicon for Low-Temperature Wafer Bonding

Abstract: A comparison of Si surface treatments for hydrophobic wafer bonding was conducted. Surface energies were found for wafers with preactivation treatments consisting of UV and heat exposure. Bonded hydrogen-terminated silicon (100) which was activated simultaneously with short-wavelength (158nm) UV/heat and bonded in an inert (normalN2) environment showed the highest bond strengths. The results are consistent with other studies of the dynamics of hydrogen on silicon (100).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Shi et al and Kub et al [119][120][121][122][123] systematically studied the effect of UV irradiation on Si/Si wafer bonding. The effect of UV irradiation time on the RMS of the Si surface and on bonding strength was investigated, as shown in figure 18.…”
Section: Ultraviolet-activated Bondingmentioning
confidence: 99%
“…Shi et al and Kub et al [119][120][121][122][123] systematically studied the effect of UV irradiation on Si/Si wafer bonding. The effect of UV irradiation time on the RMS of the Si surface and on bonding strength was investigated, as shown in figure 18.…”
Section: Ultraviolet-activated Bondingmentioning
confidence: 99%
“…Bonding mechanism discussion.-According to published articles, UV/O 3 irradiation presents two crucial impacts on the bonding surfaces: (1) removing organic contaminants [17][18][19][20][21] and (2) producing hydroxyl on surfaces (see Reactions 3 and 4). 22 The 172-nm wavelength VUV used in the experiment has been reported that can bring about 200% photo efficiency for oxygen radicals and ozone cleaning production in air.…”
Section: Resultsmentioning
confidence: 99%
“…(1) removing organic contaminants and (2) creating oxide layers on surfaces. [13][14][15][16] For the short 172-nm wavelength VUV, there is essentially 200% photo efficiency for oxygen radicals and ozone cleaning production in air. 12 Therefore, VUV cleaning is much faster than mercury UV lamp cleaning (coexistence of longer wavelengths of 254 nm and 185 nm).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, UV/O 3 irradiation may benefit direct bonding without the bombardment effect. [13][14][15] Recently, a shorter-wavelength vacuum ultraviolet (VUV) irradiation has been found to clean the surface more effectively and thereby applied for the homogenous bonding of Au/Au as well as the heterogeneous bonding between polyether ether ketone (PEEK) and Pt. 16,17 Nevertheless, little attention has been dedicated on direct homo/heterogeneous bonding of silicon and glass using VUV irradiation.…”
mentioning
confidence: 99%